Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5222/otd.2013.135
|View full text |Cite
|
Sign up to set email alerts
|

ERAS Protocol in Major Liver Resection

Abstract: Conclusion:As seen in our large series study, PNL is a highly effective and safe procedure that can be applied to the obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Patients in the accelerated surgery group were ambulated early in the first 24 hours after surgery and allowed to spend two hours out of bed on the day of surgery and six hours on the following days until they were discharged. The duration of hospitalization in this group was 5.5±1.4 days, whereas that of the conventional surgery group was 11.4±2.84 days (40). Another study stated that the duration of hospitalization was 5.7 days in patients who were ambulated early and 12.9 days in those who were not ambulated early (41).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Patients in the accelerated surgery group were ambulated early in the first 24 hours after surgery and allowed to spend two hours out of bed on the day of surgery and six hours on the following days until they were discharged. The duration of hospitalization in this group was 5.5±1.4 days, whereas that of the conventional surgery group was 11.4±2.84 days (40). Another study stated that the duration of hospitalization was 5.7 days in patients who were ambulated early and 12.9 days in those who were not ambulated early (41).…”
Section: Discussionmentioning
confidence: 73%
“…Studies have reported that the duration of hospitalization was significantly shorter in patients who were ambulated early after surgery, and that the physical, social and psychological well-being of the patients were better (16,38,39). In the study by Öndeş Bayar et al (40), patients who underwent liver resection were divided into two groups (accelerated surgery group and conventional surgery group). Patients in the accelerated surgery group were ambulated early in the first 24 hours after surgery and allowed to spend two hours out of bed on the day of surgery and six hours on the following days until they were discharged.…”
Section: Discussionmentioning
confidence: 99%